Venture capitalists' investment criteria in Poland: Entrepreneurial opportunities, entrepreneurs, and founding teams - Rafał Morawczyński (Administrative Sciences, 2020)
The aim of this article is to explore the decision-making policies by Polish Venture Capital (VC) firms, with special focus on the perception of entrepreneurs. This paper presents the results of a conjoint analysis and assessment of the importance of select characteristics among entrepreneurs and the qualities of a team of founders comprising managers of VC firms. The data were collected via face-to-face interviews with 26 Venture Capitalists. In the conjoint experiment, six attributes were presented, among which three represented characteristics of the entrepreneur (his/her passion and experience) and the management team (experience and completeness) alongside three characteristics of the opportunity (readiness of the product/service, growth rate of the market, and innovativeness of the whole project). VC managers ranked the importance of eight characteristics of the entrepreneurs related to their decisions and assessed the functional composition of the team of founders. The results of the experiment show that venture capitalists (VCs) most strongly appreciate the readiness of the product and entrepreneur's passion. However, their preferences varied across the sample. The results of the ranking also show that the VC managers highly value the honesty of the entrepreneur. VCs typically prefer a team of founders, rather than a single-person project, preferably consisting of persons at least familiar with the technology and the market. This study contributes significantly to the state-of-the-art, as research on VC investment policy (investment criteria) is relatively rare in Central and Eastern Europe, where the VC industry is starting to flourish.
Keywords: 350; Venture Capital; entrepreneurship; entrepreneurs; entrepreneurial teams; investment criteria